Passive resistance : portuguese diplomacy of contraband trade during king John V's reign, 1706-1750 - Pijning, Ernst (2010)
Submitted by RUA REPOSITORIO (repositorio@uac.pt) on 2010-04-12T15:00:33Z No. of bitstreams: 1 ErnestPijning_p171-191.pdf: 257777 bytes, checksum: 8be53abac98fb326d92972526886c7e2 (MD5)